Research, Development and Application of Hybrid Model of Back-to-Back HVDC Link - Ufa R. A. Ruslan Alexandrovich; Andreev M. V. Mikhail Vladimirovich; Diab A. A. Z. Ahmed; Gusev A. S. Alexander Sergeevich; Ruban N. Yu. Nikolay Yurievich; El Sattar M. A.; Suvorov A. A. Aleksey Aleksandrovich; Ali Ziad M.; Askarov A. B. Alisher Bakhramzhonovich; Rudnik V. E. Vladimir Evgenevich; Razzhivin I. A. Igor Andreevich; Kievets A. V. Anton Vladimirovich; et al. (2020, 2020)
Title screen